A case for genetic testing: Arrhythmogenic cardiomyopathy presenting as myocarditis - Rachelle E. Srinivas; Lydia K. Wright; Deipanjan Nandi; Emily A. Hayes (Wolters Kluwer Medknow Publications, 2024)
Arrhythmogenic cardiomyopathy (ACM) is an inherited cardiomyopathy associated with fibrofatty tissue replacement of the ventricular tissue. The disease can cause ventricular dysfunction and arrhythmias and can increase the risk of sudden cardiac death. This cardiomyopathy can have variable clinical presentations, especially in the pediatric and young adult populations. In this report, we describe the case of an 18-year-old female with myocarditis as the initial presentation of ACM. She presented following a resuscitated cardiac arrest due to ventricular arrhythmia. On arrival, myocardial edema and delayed gadolinium enhancement were present on cardiac magnetic resonance imaging, with no ventricular changes observed, making the diagnosis consistent with myocarditis. Genetic testing revealed a pathogenic mutation in the desmoplakin gene consistent with ACM. Given the unconventional initial presentation of this patient's disease, early consideration of genetic testing may be beneficial to aid in the early diagnosis and management of ACM in young patients.